2007
DOI: 10.1111/j.1467-971x.2007.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

English in Germany: contact, spread and attitudes

Abstract: The majority of studies examining English in Germany have been rather narrow in focus, addressing largely the phenomenon of Anglicisms in the German language. In the late 1980s, however, scholars began looking beyond Anglicisms to consider the broader topic of the English language in the German context. This paper presents a qualitative, macrosociolinguistic profile of English in the largest of the German-speaking countries, and also Europe's most powerful economy, the Federal Republic of Germany. Utilizing Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 20 publications
(7 reference statements)
1
39
0
Order By: Relevance
“…Taking into account other studies demonstrating the growing use of English as an additional language in German education (Hilgendorf 2005;Erling/ Hilgendorf 2006) and business (Hilgendorf 2010a), as well as overviews of the history of contact with the language (Hilgendorf 2007(Hilgendorf , 2010b, this study provides further evidence of the expanding role of English in Germany, if not other European countries, and the language's shifting status from that of a foreign language to an additional language (L2) as reflected in the social reality of its users and uses. In an additional observation, it should be noted that this …”
Section: Discussionmentioning
confidence: 99%
“…Taking into account other studies demonstrating the growing use of English as an additional language in German education (Hilgendorf 2005;Erling/ Hilgendorf 2006) and business (Hilgendorf 2010a), as well as overviews of the history of contact with the language (Hilgendorf 2007(Hilgendorf , 2010b, this study provides further evidence of the expanding role of English in Germany, if not other European countries, and the language's shifting status from that of a foreign language to an additional language (L2) as reflected in the social reality of its users and uses. In an additional observation, it should be noted that this …”
Section: Discussionmentioning
confidence: 99%
“…The role of English in Germany has been studied by Stefanowitsch (2002) and Hilgendorf (2007). The role of English in Germany has been studied by Stefanowitsch (2002) and Hilgendorf (2007).…”
Section: Is This Approach Relevant For the German Elt Classroom?mentioning
confidence: 99%
“…Hilgendorf (2007) suggested that although there are numerous factors opposing the spread of English, including a lengthy history of negative attitudes towards foreign linguistic elements, in reality, judging from the extent to which English is used in society every day, the positive attitudes clearly succeed in overcoming whatever prejudices that society has towards learning English. Thus it is important that even students in Malaysia should have a positive attitude towards English language so that they may not be influenced by any antagonism towards the language by any sector of the society.…”
Section: Attitude Towards Learning English Languagementioning
confidence: 99%